CARTOGRAFIA HISTÓRICA E GEOPROCESSAMENTO: O EXEMPLO DOS MAPAS DOS PADRES MATEMÁTICOS, DE 1734, E DO CÁLCULO DE RENDIMENTOS GERAIS DO BISPADO DE MARIANA, DE 1752 - Castro, José Flávio Moraes (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2014)
The historical maps has been the subject of special interest to researchers in a variety of areas, due to its importance as a record of the cultural values of the society in space and time. This work aims to analyze the interfaces between the Historical Cartography and GIS, adopting, with example, the georeferencing and vectorization of maps of the Captaincy of Minas Gerais developed by mathematicians priests Diogo Soares and Domingos Capassi in 1734. It is intended to also represent the calculation of general revenues of the Bishopric of Mariana, 1752, through thematic maps. We propose a methodological for use of GIS in historical information, based on the principles of "Graphic Semiology" for the treatment of spatial information.